Organizational Climate and Attitude Towards Work Among Law Enforcers - Llyond John Quilla; Ariel Alamban (Research Synergy Foundation, 2025)
This study aimed to examine the relationship between organizational climate and work attitudes among law enforcers, focusing on reward systems, career development, and organizational direction, as well as work-related attitudes such as commitment, compensation satisfaction, and corporate communication. A quantitative, descriptive–correlational research design was employed, with data collected through a structured survey administered to law enforcement personnel. Descriptive and inferential statistical analyses, including correlation and regression, were used to analyze the data. Results indicated that law enforcers generally perceived their organizational climate positively, particularly in recognition, rewards, and clarity of organizational direction, while career development received lower ratings. A strong and statistically significant relationship was found between organizational climate and attitudes toward work (r = 0.835, p < 0.001). Further analysis revealed that reward systems and organizational direction were the strongest predictors of work attitudes, jointly explaining 78.5% of the variance. These findings highlight the importance of fostering a supportive organizational climate to enhance law enforcers’ job satisfaction, commitment, and performance. This study contributes empirical evidence to the literature on organizational climate within the law enforcement context and offers practical insights for organizational policy and human resource development.